2008
DOI: 10.1002/esp.1691
|View full text |Cite
|
Sign up to set email alerts
|

The potential of digital filtering of generic topographic data for geomorphological research

Abstract: High resolution terrain models generated from widely available Interferometric Synthetic Aperture Radar (IfSAR) and digital photogrammetry are an exciting resource for geomorphological research. However, these data contain error, necessitating pre-processing to improve their quality. We evaluate the ability of digital filters to improve topographic representation, using: (1) a Gaussian noise removal filter; (2) the proprietary filters commonly applied to these datasets; and (3) a terrain sensitive filter, simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Thus, there are a number of valid types and specific uses of synthetic DEMs, but in combination we believe that they form a vital underpinning for the quantitative future of landform analysis (e.g. see McCoy, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there are a number of valid types and specific uses of synthetic DEMs, but in combination we believe that they form a vital underpinning for the quantitative future of landform analysis (e.g. see McCoy, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Rigour added to geomorphological observations through testing with synthetic DEMs will, we believe, ultimately link physics-driven models of processes to morphological observations, allowing quantitative hypotheses to be formulated and tested (e.g. see McCoy, 2015). This is illustrated in Fig.…”
Section: Synthetic Tests and The Potential Uses Of Synthetic Demsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that a vertical accuracy of ± 0.02 m could be obtained for a dry bar surface. In another study, the point density of the static TLS varied between 100 and 10 000 points/m 2 mainly due to changes in the range to the target and an RMS error ranging from ± 2 to ± 25 mm (Milledge et al, 2009). Milan et al (2007) concluded that TLS makes it possible to identify faint changes in fluvial geomorphology, including change detection of the bar edges, banks, chute channels and lobe deposition.…”
Section: Laser Scanning Methods For Acquiring Topographic Data In Flumentioning
confidence: 99%
“…English Heritage have proposed a series of standard scanning resolutions for representing specifi c scales of change on stonework (English Heritage, 2007). Use of high resolution remotely sensed data for representing terrain has become increasingly common across a range of scales (Lane and Chandler, 2003), in particular the use of digital photogrammetry (Lane et al, 2000;Bailey et al, 2003), detailed GPS survey (Brasington et al, 2000), LiDAR (Glenn et al, 2006;Notebaert et al, 2009;Mitasova et al, 2009) as well as combinations of these techniques and consideration of the associated potential errors (Lim et al, 2005;Dewitte et al, 2008;Milledge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%